Preliminary study: comparison of 2 different techniques in recurve archery - Sien, Lau Jiun (Universiti Sains Malaysia, 2016)
The purpose of this study is to compare the effect of two different archery methods on the shooting performance. The participants are four male recurve archers from Kelantan who volunteered to join this study. Pre and post-test scores of the total points for 36 arrows shot at 10 meters and 30 meters were collected. 3D motion analysis (Qualysis) system was used to record the method of the archers (stance, posture and shoulder alignment) and it was measured simultaneously. After a familiarisation period to the body markers and testing environment, the participants were asked to shoot 36 arrows with their method at a distance 10m and 30m. Then, the participants were taught the BEST method and were given one week to be familiar with the method. The scores were collected again at 10m and 30m with the BEST method. The methods of recurve archery were further broken down to 10 steps for analyses. Wilcoxon signed rank test was used to detect the difference between their own method and BEST method based on 3D motion analysis data. Most of the participants showed significant changes in the shooting steps, 8 steps out of 10 steps showed significant differences (p<0.05). This showed that the BEST method is different from the participants’ method. The changes used in the method showed the improvement in the shooting performance. Most of the participants showed improvement in the score for 10 meter and 30 meter as well as the distance of the arrow away from the centre based on the (p<0.05). Thus, from the result, it can be concluded that BEST method able to improve the participant performance.